A rendszerváltás antropológiája Magyarországon és „Somogyországban” - Bertalan, Péter (Acta Scientiarum Socialium, 2012)
The essay analyzes the political, the economic and social aspects of the change of the Kádár-regime. It introduces the economic contradictions of the change of the Kádár-system. It emphasizes the social contradictions of our everyday lives and it places great emphasis on the discussion of the morality and immorality which is taking place in our society from the aspects of privatizations and the separation of our society. 1989 was a turning point int the history of Central Europe. The historian prefer using the term „revolution” in these times. This change was considered to be a peaceful transition. The historic tragedy of Central European countries is that there is no continuity in property relations. The idea of social solidarity often suffers serious injuries, which often leads to social immorality both in politics and economy.
Keywords: morality and immorality; the aspects of privatizations; social solidarity